Strategic planning of educational actions on Hypertension and Diabetes in Primary Care: Experience report (Research, Society and Development, 2021)
Objective: To report the experience lived in the planning of educational actions on Hypertension and diabetes carried out with elderly people in primary care, using the conversation wheel strategy. Method: This descriptive study deals with an experience report on the use of the conversation wheel as a strategy for planning health education activity with elderly users, in the context of practical theoretical teaching of nursing management discipline I, in the first half of 2019 in a health unit in the city of Niterói-RJ, linked to the Unified Health System. Results: The conversation wheel is a satisfactory strategy since the target audience living with hypertension and diabetes had the opportunity to expand their perspectives to make better decisions and improve their quality of life resulting from the exchange of knowledge of topics of interest to users. Conclusion: The planning of the activities of the conversation wheel as a strategy to achieve the objectives of promoting the health of hypertensive and diabetic elderly, provided active participation of them, with exchanges of information aimed at the development of the individual's autonomy and the reduction of damages. With regard to students, it brought clarity of their role in the planning and organization of their practice, as well as greater security in their approaches as future professionals responsible for education in user and community health.